Servicescape, guest satisfaction, and intention to book a hotel room - Tarmudi, Sabrina; Jaharuddin, Nor Siah (Human Resource Management Academic Research Society, 2021)
Servicescape role in the service industry is increasingly important and getting attention in the hospitality research, however less attention has been given specifically on physical servicescape and guest satisfaction towards the intention to book a hotel room. The purpose of this research is to study the operationalize construct of physical servicescape. Drawing on Stimulus-Organism-Response (SOR) theory, this study aims to examine the relationship between physical servicescape and guest satisfaction towards the intention to book a hotel room behavior. A quantitative study by distributing questionnaires to hotel guest who experienced the physical servicescape at the hotel will be employed. Analysis of the data collected by using Structural Equation Modeling (SEM) will be used to test the hypothesized relationships among variables. In addition, it is hoped that this study will sheds new lights on the relationship between physical servicescape and guest satisfaction towards intention to book. The theoretical and practical implications will be discussed.